Empowering South Sulawesi MGMP Economics Teachers through Digital Economic Literacy and Artificial Intelligence: Pemberdayaan Guru Ekonomi MGMP Sulawesi Selatan melalui Literasi Ekonomi Digital dan Artificial Intelligence - Nurhayani, Nurhayani; Ryketeng, Masdar; Akbar, Muh.; Fakhri, M. Miftach; Rauf, Annajmi; Awalia, Andi Dio Nurul; Isma, Andika (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
The transformation of education in the digital era requires teachers to have adequate technological literacy, especially in economic learning that is relevant to the dynamics of everyday life. This service program aims to improve teachers' digital economic literacy through a Kahoot-based game-based learning approach. Four main materials were developed, namely Shares, Online Gambling, Life Trail, and MagicSchool AI. The activity was carried out with the South Sulawesi Economics Teacher MGMP Forum using a Participatory Action Research (PAR) approach through the stages of socialization, training, implementation, mentoring, and evaluation. The methods used were interactive quizzes, simulations, discussions, and hands-on practice. The evaluation results showed a significant increase in teachers' understanding, with the highest achievement in the material of Shares and MagicSchool AI. This training not only strengthens teachers' digital skills, but also fosters their reflective, collaborative attitudes and readiness as agents of change in integrating digital technology in economic learning.